The Doron Wars and Building New Strategies in the Middle East Managing the Iranian Israeli Conflict as a Case Study (Journal of Political Science and International Relationship, 2025)
This study examines the strategic effects of drone warfare in the Middle East, focusing on Iran-Israel relations. UAVs’ rapid development and use have revolutionized military tactics, improving surveillance, reconnaissance, and precise strikes. Iran uses unmanned aerial vehicles (UAVs) to project force and use asymmetrical warfare. However, Israel uses advanced drone technology for intelligence gathering and precision assaults. This paper explores the strategic employment of unmanned aerial vehicles (UAVs), their impact on regional stability, and the efficacy of numerous UAV-defeating technologies. UAV ethical and legal issues are also covered. In order to mitigate the risks of widespread UAV use, regions must cooperate, build detailed legal structures, and allocate resources to counter-drone technologies.